Sorption of Palladium onto Bentonite, Illite and Shale Under High Ionic Strength Conidtions - Riddoch, Justin (My University, 2016)
Both crystalline and sedimentary rocks are being considered as potential host rocks for a deep geological repository in Canada. Deep-seated sedimentary rocks in the Michigan Basin, Ontario, Canada contain highly saline ground and pore waters. The relatively high I of these waters may influence speciation and rock matrix sorption properties. To this end, laboratory sorption experiments were conducted to examine sorption of Pd(II) on sodium bentonite, illite and Ordovician age shale as a function of pH and solution I and initial concentration of Pd. Solutions with pH values in the range of 5 to 9, I ranging from 0.1 to 4 M and initial concentration of Pd ranging from 5×10 −8 to 1×10 −6 M were considered. A sorption time of 14 days was used and the separation method was by centrifuge. Experiments were performed under aerobic conditions at 25 ◦ CC, and the Eh value of the solution ranged from 300 to 600 mV. The data from sorption experiments were used to validate surface complexation models developed in PHREEQC with the JAEA TDB. The sorption of Pd on bentonite, shale and illite all showed strong dependence on I and pH. The dependence on initial concentration of Pd was used to plot sorption isotherms. The slope of the isotherms showed that Pd was forming inner- and outer- sphere complexes inside the stern layer for sorption onto bentonite and illite. It also showed however that shale was most likely undergoing cooperative sorption. Strong fit was found between the single layer surface complexation model for montmorillonite (the major constituent clay mineral of sodium bentonite) and experimental data, but not for illite (the major constituent clay mineral of shale).
Keywords: Sorption; Palladium; Speciation; Bentonite; Illite; Shale